Bank efficiency, market concentration and economic growth in the European Union - Ferreira, Cândida (2012)
Well-functioning financial markets and banking institutions are usually considered to be a condition favourable to economic growth. The importance of bank efficiency and bank market concentration has also been the object of discussion, with the general belief that while they are of particular relevance in the context of the European Union, there is no consensus on their specific roles. This paper aims to study the effects on economic growth of the efficiency of the banking institutions, measured through Data Envelopment Analysis (DEA), and also of the concentration of the bank markets, measured by the percentage share of the total assets held by the three largest banking institutions (C3) and the Herfindahl-Hirschman Index (HHI). Considering a panel of all 27 EU countries for the time period between 1996 and 2008, the study analyses the influence of these bank and market conditions not only on the Gross Domestic Product (GDP) but also on its components: the final consumption expenditure, the gross fixed capital formation, the export of goods and services and the import of goods and services. The main findings point to the generally positive influence of bank cost efficiency on economic growth. More precisely, this influence is statistically significant for GDP and particularly with respect to the gross fixed capital formation. With regard to the bank market concentration, a generally negative influence is revealed, not only on GDP, but also on its components and is statistically more significant for the gross fixed capital formation, as well as for the export and import of goods and services.